2004
DOI: 10.1073/pnas.0306666101
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized thymic lobe transplantation in miniature swine: Thymopoiesis and tolerance induction across fully MHC-mismatched barriers

Abstract: As the major site of self-nonself discrimination in the immune system, the thymus, if successfully transplanted, could potentially carry with it the induction of central tolerance to any other organ or tissue from the same donor. We have recently developed a technique for transplantation of an intact, vascularized thymic lobe (VTL) in miniature swine. In the present study, we have examined the ability of such VTL allografts to support thymopoiesis and induce transplantation tolerance across fully MHC-mismatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 22 publications
2
88
2
Order By: Relevance
“…FK506 has been found previously not to have measurable effects on thymus structure or involution in miniature swine (13). The morphometric analysis of aged thymus grafts transplanted into juvenile recipients revealed marked rejuvenation of these grafts within two months of transplantation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FK506 has been found previously not to have measurable effects on thymus structure or involution in miniature swine (13). The morphometric analysis of aged thymus grafts transplanted into juvenile recipients revealed marked rejuvenation of these grafts within two months of transplantation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3 and SI Fig. 7) or juvenile MHC-mismatched VTLs (13). Aged MHC-mismatched VTL grafts were still hypocellular on day 60, but thymic stromal cells were present without vasculitis ( Fig.…”
Section: Aged Vtls Induce Transplant Tolerance Across Mhc Disparate Bmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, keratinocyte growth factor and sex steroid ablation have been reported to improve thymopoiesis by restoration of the functions of thymic epithelial cells [8][9][10][11][12][13]. Transplantation of cultured thymus fragments has been used to provide the thymic microenvironment for T-cell regeneration in patients and experimental animals with T-cell deficiencies or as a method for the induction of tolerance in organ transplantation [7,[14][15][16][17]. Studies on thymus organogenesis in the murine embryo have indicated that both the cortical and medullary epithelial cells arise from a common progenitor population [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of keratinocyte growth factor or sex steroid ablation has been shown to increase the number of TECs, resulting in enhanced thymopoiesis (Kelly et al, 2008;Min et al, 2002;Min et al, 2007;Alpdogan et al, 2006). Additionally, transplantation of cultured thymus fragments has been used to provide the thymic microenvironment for T-cell regeneration in patients and experimental animals with T-cell deficiencies or as a method for the induction of tolerance in organ transplantation (Markert et al, 2003;Hong et al, 1979;Yamada et al, 2000;Kamano et al 2004). However, the applications of cultured thymus fragments are limited by tissue availability.…”
Section: Introductionmentioning
confidence: 99%